2005
DOI: 10.1080/09602010443000443
|View full text |Cite
|
Sign up to set email alerts
|

Assessing level of consciousness and cognitive changes from vegetative state to full recovery

Abstract: Although investigations addressing cognitive recovery from the vegetative state have been reported, to date there have been no detailed studies of these patients combining both neuropsychology and functional imaging to monitor and record the recovery of consciousness. This paper describes the recovery of a specific vegetative state (VS) case. The patient (OG) remained in the vegetative state for approximately two months, increasing her level of awareness to a minimally conscious state, where she continued for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 24 publications
0
32
1
7
Order By: Relevance
“…The fMRI study performed after recovery showed more widespread activation encompassing the language networks. 17 Using a hierarchical auditory stimulation paradigm in fMRI, Coleman et al 13 reported seven VS patients, three of whom (one traumatic and two non-traumatic) showed temporal activation in the low-level auditory contrast (all sounds versus silence) and mid-level speech perception contrast (meaningful speech versus signal-correlated noise). 18,19 The remaining four patients showed no activation in response to sound compared with silence.…”
Section: Atypical 'Higher Order' Associative Cortical Activation In Vsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fMRI study performed after recovery showed more widespread activation encompassing the language networks. 17 Using a hierarchical auditory stimulation paradigm in fMRI, Coleman et al 13 reported seven VS patients, three of whom (one traumatic and two non-traumatic) showed temporal activation in the low-level auditory contrast (all sounds versus silence) and mid-level speech perception contrast (meaningful speech versus signal-correlated noise). 18,19 The remaining four patients showed no activation in response to sound compared with silence.…”
Section: Atypical 'Higher Order' Associative Cortical Activation In Vsmentioning
confidence: 99%
“…All in all, eight PET studies including 32 patients [6][7][8][9][10][11]16,18,23 and six fMRI studies including 17 patients 12,13,15,[17][18][19][20][21] (one patient was studied by both PET and fMRI) have been reviewed (Table 1). Among these 48 patients (16 of whom were traumatic), 25 patients (52%; 8 traumatic) showed typical activation patterns, five patients (10%; 1 traumatic) showed no activation and 18 patients (38%; 7 traumatic) showed atypical activation patterns.…”
Section: Does Cerebral Activation Predict Clinical Recovery?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some MCS patients may retain widely distributed cortical systems with potential for cognitive and sensory function, despite their inability to follow simple instructions or communicate reliably (Schiff et al , 2005). PET and fMRI case reports incorporating complex auditory stimuli have shown large-scale network activation in the minimally conscious state that is not observed in unconscious vegetative patients (Bekinschtein et al , 2005, Laureys et al , 2004b.…”
Section: Auditory Function Scalementioning
confidence: 99%
“…In some fMRI or/and PET studies, patients with higher-level associative cortical activation in VS progressed to MCS or recovered consciousness (Bekinschtein, Tiberti, 2005, Coleman et al , 2007, Di et al , 2007, which seem to show that atypical 'higher order' associative cortical activation in VS heralds recovery of some level of consciousness some months later. Other VS patients with 'higher level' associative cortical activation failed to subsequently recover (Staffen et al , 2006), which was in line with the viewpoint that VS patients with atypical behavioral fragments can show residual isolated brain processing in the absence of clinical recovery (Schiff et al , 2002) .…”
Section: Auditory Function Scalementioning
confidence: 99%